2017
DOI: 10.1051/matecconf/201710905001
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in a Loop Heat Pipe Using Fe2NiO4-H2O Nanofluid

Abstract: Abstract. Nanofluids are stable suspensions of nano fibers and particles in fluids. Recent investigations show that thermal behavior of these fluids, such as improved thermal conductivity and convection coefficients are superior to those of pure fluid or fluid suspension containing larger size particles. The use of enhanced thermal properties of nanofluids in a loop heat pipe (LHP) for the cooling of computer microchips is the main aim of this study. Thus, the Fe2NiO4-H2O served as the working fluid with nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Gunnasegran et al, [11] Fe2NiO4 -water An average decrease of 5.75 o C (14%) was achieved in core temperatures of desktop PC CPU using Fe2NiO4-H2O Sarafraz et al, [12] Liquid gallium CuO-water Results demonstrated that both coolants present a higher thermal performance in comparison with water. Gallium showed superior thermal performance compared to nanofluid.…”
Section: Recent Application Of Nanofluid On Electronics Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gunnasegran et al, [11] Fe2NiO4 -water An average decrease of 5.75 o C (14%) was achieved in core temperatures of desktop PC CPU using Fe2NiO4-H2O Sarafraz et al, [12] Liquid gallium CuO-water Results demonstrated that both coolants present a higher thermal performance in comparison with water. Gallium showed superior thermal performance compared to nanofluid.…”
Section: Recent Application Of Nanofluid On Electronics Coolingmentioning
confidence: 99%
“…From the literature reviews, it is confirmed that a higher concentration of nanofluid has better heat transfer performance. Unfortunately, most of the studies just use a small percentage of nanofluid approximately <5% concentration in the liquid system [10,11,22]. One of the considerations of the selected concentration is the stability of nanofluid.…”
Section: Recent Application Of Nanofluid On Electronics Coolingmentioning
confidence: 99%